Effect of Computer Mediated Communication and Face-to-Face Communication on the Students’ Writing - Vita Vendityaningtyas; Erlik Widiyani Styati (Lingua Cultura, 2018)
This research aimed to investigate the effect of computer-mediated communication (CMC) and face-to-face (F2F) communication on the students’ writing. The subjects were the English department students of the fourth semester at the private University in Madiun. The researchers employed the students in class A and B as the research subjects. The research method used was a quasi-experimental design. The research design was divided into pre-test, treatment, and post-test. Both of the two groups were given pre-test to see the homogeneity of the two groups. The experimental group was given CMC, and the comparison group was given F2F communication. Then, both of the two groups were given post-test. The data collection technique was done by giving the students a writing test. Data analysis was done by employing the independent t-test. The result shows that the students’ writing after employing F2F communication is more effective than students’ writing after employing CMC. The students like to share the ideas directly than they employ CMC because it is more complicated. In addition, it is because the students find difficulty in sharing the ideas through CMC, so, F2F communication is better than CMC on the students’ writing quality.